(untitled) (Studia Prawnicze / The Legal Studies, 2011)
Koncepcja chronionej prywatności kryje w sobie sprawy związane z wolnością sumienia i wyznania, preferencji seksualnej, swobody wyrażania poglądów, nietykalność mieszkania. Nie istnieje żadna spójna i powszechnie akceptowana defi nicja sfery życia prywatnego. Każdej z tych sfer dotyczyło wiele orzeczeń Trybunału Praw Człowieka w Strasburgu. Podstawą tych rozstrzygnięć był najczęściej art. 8 Europejskiej Konwencji o Ochronie Praw Człowieka i Podstawowych Wolności. Konstytucja RP również nie zawiera definicji prywatności, choć w art. 47 stanowi ogólnie, że “Każdy ma prawo do ochrony prawnej życia prywatnego”. Sfera prawnie chronionej prywatności nie powinna być zasadniczo odmiennie rozumiana zakresowo w rozmaitych gałęziach prawa. Nadrzędna pozycja normy konstytucyjnej stwarza odpowiednią podstawę dla poszukiwania wspólnych, uniwersalnych elementów. Z drugiej strony ogranicza prawo władz publicznych związane ze zbieraniem informacji o obywatelach (art. 51). Również ustawa z 29 sierpnia 1997 roku o ochronie danych osobowych4 chroni pewną autonomię człowieka, zakazując przetwarzania i gromadzenia danych, np. dotyczących jego preferencji seksualnych (art. 27), co wydaje się dotyczy również osób publicznych. Można stąd wywnioskować, iż istnieje “przestrzeń, domena nieosiągalności” dla innych, gdzie prawo do informacji schodzi na plan dalszy. One of the interests protected by the law is an individual’s privacy. We should also remember that, most of all, it is an individual himself who always remains a decision-maker while determining the scope of his privacy to be protected, and this is his right within informative autonomy that remains the crucial point of reference for legal evaluations. It does not mean that there are no exceptions to this, nevertheless, the scope of press invasion of this sphere of human life is determined unanimously either by the legislator (as it is in the Polish law – Art. 14 par. 6 of the PL, or in the Lithuanian Civil Code - Art. 2.23 § 3) or by the court jurisdiction. Circumstances of private and family life include such spheres of life with reference to which social interest does not cause the state’s invasion. The sphere of private life is subject to special legal protection. A principle banning dissemination of information from the sphere of privacy in the mass media should be adopted. Invasion of this sphere of life is exceptionally admissible under Art. 14 par. 6 of the PL when a specific behavior of a criticized person, which he/she has been accused of, goes beyond the boundaries of private or family life in its strict sense, and directly influences a public activity. In the case of invasion of the sphere of privacy, the issue whether the allegations are true recedes into the background. The first criterion of the investigation should be the question whether social usefulness of given facts justifies publication of information about an individual’s personal life in the media. The provision of Art. 14 par. 6 of the PL allows publication of information about an individual’s private life only if it is directly connected with his/her activity. It is assumed that some facts from an individual’s life must be capable of contributing to the evaluation of actions he/she is carrying out within his/her public activity. A degree of privacy does not matter here (more or less intimate relations) but the fact whether revealed information from an individual’s life may impact on the way they are conducting their public activity. It should be added that the jurisdiction of the European Court protects private life of, e.g. a politician, too. Family and private life is still subject to protection even though public opinion has the right to learn about such matters but only those which are connected with politicians’ official position or those that influence the evaluation of their credibility.